2011
DOI: 10.3892/ol.2011.289
|View full text |Cite
|
Sign up to set email alerts
|

Treatment strategies in intermediate cervical neoplasia: Implications of radical surgery

Abstract: Abstract. Treatment strategies for cervical intraepithelial neoplase (CIN)2 lesions differ among gynaecologists. To evaluate the differences in management of treatment with subsequent implications, all surgical treatment strategies and follow-up methods were retrospectively analysed for patients with intermediate dysplasia of the cervix. This study aimed to evaluate expectant management strategies and the effect of biopsy prior to radical surgery in CIN2. Patients diagnosed with a CIN2 lesion at the Orbis Medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…We identified 250 potentially eligible studies; 43 publications met the inclusion criteria (fig 1),6222324252627282930313233343536373839404142434445464748495051525354555657585960616263 but seven were duplicate reports of the same data 27283140505254. Of the 36 eligible studies (total of 3160 women), seven (19%) were randomised trials with suitable data in the non-experimental arm,22253339455762 16 (44%) were prospective cohort studies,6263032343536373841435155566063 and 13 (36%) were retrospective cohort studies23242942444647484953585961 (see supplementary table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified 250 potentially eligible studies; 43 publications met the inclusion criteria (fig 1),6222324252627282930313233343536373839404142434445464748495051525354555657585960616263 but seven were duplicate reports of the same data 27283140505254. Of the 36 eligible studies (total of 3160 women), seven (19%) were randomised trials with suitable data in the non-experimental arm,22253339455762 16 (44%) were prospective cohort studies,6263032343536373841435155566063 and 13 (36%) were retrospective cohort studies23242942444647484953585961 (see supplementary table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 36 eligible studies (total of 3160 women), seven (19%) were randomised trials with suitable data in the non-experimental arm,22253339455762 16 (44%) were prospective cohort studies,6263032343536373841435155566063 and 13 (36%) were retrospective cohort studies23242942444647484953585961 (see supplementary table 2). The median follow-up was 16 months (range 3-72, interquartile range 7.6-27.4 months).…”
Section: Resultsmentioning
confidence: 99%
“… 31 Van Delft et al showed that among 109 CIN1 patients who underwent colposcopy, 47.71% were combined with CIN2 or worse. 32 In addition, Kinney et al and Barut et al reported that CIN3 is often missed or misdiagnosed as CIN1 or CIN2 using cytology and colposcopy in the initial screening procedure, because of low sensitivity and specificity, or sometimes due to poor technique, incorrect biopsy site, or the presence of multiple lesions with different grades of CIN. 33 , 34 Thus, for patients with the endpoint diagnosis of CIN1, how to avoid missing higher‐grade lesions while avoiding overtreatment has become a crucial challenge among gynecologists.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous reports, in the cases diagnosed as CIN1 under colposcopy biopsy, the missed diagnosis rate of CIN2 and higher‐grade lesions is 19%–55% 31 . Van Delft et al showed that among 109 CIN1 patients who underwent colposcopy, 47.71% were combined with CIN2 or worse 32 . In addition, Kinney et al and Barut et al reported that CIN3 is often missed or misdiagnosed as CIN1 or CIN2 using cytology and colposcopy in the initial screening procedure, because of low sensitivity and specificity, or sometimes due to poor technique, incorrect biopsy site, or the presence of multiple lesions with different grades of CIN 33,34 .…”
Section: Discussionmentioning
confidence: 99%